Stable Flies, Stomoxys calcitrans L. (Diptera: Muscidae), Improve Offspring Fitness by Avoiding Oviposition Substrates With Competitors or Parasites - Baleba, Steve B. S.; Torto, Baldwyn; Masiga, Daniel; Getahun, Merid N.; Weldon, Christopher W. (Frontiers in Ecology and Evolution, 2020)
Oviposition site selection by gravid female insects is an important determinant in species distribution, abundance, and population dynamics. Females may assess the suitability of a potential oviposition substrate by using cues from conspecific or heterospecific individuals already present. Here, we assessed whether the presence of conspecific or heterospecific larvae and parasites influenced oviposition decisions by the stable fly, Stomoxys calcitrans (Linneaus). Using dual and multiple-choice oviposition bioassays, we found that gravid female S. calcitrans avoided substrates with conspecific larvae, the larvae of house flies, Musca domestica (Linneaus), and the mite Macrocheles muscaedomesticae (Scopoli). Avoidance of conspecific and heterospecific larvae persisted in the dark, suggesting that this behaviour is mediated by chemical rather than visual cues. When we reared S. calcitrans in the presence of conspecific larvae and the larvae of house flies at different densities we found that this negatively affected emergence time, larval weight, larval survival, pupal weight, pupal survival, and adult weight. We also demonstrated that individuals of S. calcitrans developed in the presence of mites exhibited low egg hatchability, and poor larval and adult survival. Our study provides additional support for the “preference-performance” hypothesis in S. calcitrans, with gravid females preferring to lay eggs on a substrate that will enhance offspring fitness. We recommend that the chemical cues involved in avoidance by gravid female S. calcitrans of substrates with conspecific and heterospecific larvae should be elucidated. This could lead to the discovery of repellent chemicals important for S. calcitrans management.